Clinico-Radiological Presentation and Outcome of Brain Abscess in Congenital Cyanotic Heart Disease - Sedain, Gopal; Bohara, Sandeep; Shrestha, Dipendra Kumar; Pradhanang, Amit Bahadur; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Journal of Institute of Medicine Nepal, 2024)
Introduction Patients with congenital cyanotic heart disease (CCHD) are at increased risk of developing brain abscesses. Having a brain abscess is itself a risk for the patient and concomitant cyanotic heart disease makes it a double jeopardy. The management of brain abscesses depends on the size, number, stage, and location of the abscess and can be medical and surgical. Methods This retrospective chart review was conducted at Tribhuvan University Teaching Hospital, Kathmandu, Nepal of patients treated between January 2018 and December 2022. Demographic and clinical profiles, imaging studies, treatment modalities, and outcomes were analyzed. Results Out of 17 patients, 11 were males and six were females. The mean age of the study population was 13.41±11.08 years. The most common associated cardiac problem was Tetralogy of Fallot seen in six (35.3%) patients and the most common abscess site was the parietal lobe (38%). The most common presenting symptom was vomiting, seen in 76%. Twelve patients underwent burr hole and aspiration and 17.6% of patients underwent surgical excision of the abscess wall whereas 11.7% of the patients were managed conservatively. Positive culture was seen in 33.3%. S. aureus was the most common organism grown. There was no mortality. Conclusion Majority of patients were male with Tetralogy of Fallot as the most common associated congenital cardiac condition. Most of the patients were managed with Burr hole and abscess aspiration with re-aspiration in three patients. Suspicion of brain abscess should be high in patients with congenital cyanotic heart disease.